Methods of motivation capacity Group Reluctance Negative Information-Psychological Influence upon Interior Troops enlisted man in composition Department of Territorial Command - Drobakha H. А.; Lіpatov І. І.; Hunbіn K. Yu.; Lіpatova S. L. (Honor and Law, 2019)
Approaches to motivation of number of the group reluctance negative information-psychological influence Interior Troops enlisted man are defined as a result of analysis contents its work.